Terraform core functionality. (Pearson, 2023)
7+ Hours of Video Instruction Learn the power of Infrastructure as Code with Terraform. Terraform Core Functionality enables you to orchestrate your infrastructure effortlessly, ensuring scalability, consistency, and efficiency. You will be able to create seamless code allowing you to manage and deploy cloud resources across platforms. Highlights include learning how to write Terraform configurations, and how to work with variables and modules. In addition, learn advanced Terraform concepts such as logging, and troubleshooting, expressions, functions, and meta-arguments. Author and instructor Dave Prowse will show you how to install and use Terraform to build cloud-based infrastructure efficiently. Topics include: Terraform Variables Terraform Modules Terraform Logging and Troubleshooting Working More and Providers Terraform Language Advanced Terraform The step-by-step labs for this course are available at https://github.com/daveprowse/tac-course. About the Instructor: Dave Prowse has more than 20 years of experience in the IT field. He solves problems for organizations using Linux, infrastructure as code, and many other types of technology. He loves to teach those solutions to others. Dave is an advocate of lifelong learning, self-improvement, building confidence, and the sharing of knowledge. You can contact Dave at his website: prowse.tech. Skill Level : Beginner to Intermediate Learn How To: Understand Terraform fundamentals including Terraform Cloud, Terraform Language Log and troubleshoot Terraform Use Advanced Terraform Set up Infrastructure as Code Using Terraform Course requirement: Recommended: A virtual machine running Linux An IDE (such as Visual Studio Code) Knowledge of the terminal Access to GitHub Recommended: An AWS account with a separate IAM user that has administrative permissions. Who Should Take This Course: Anyone interested in studying for and passing the Certified Terraform Associate exam. Cloud engineers, software developers, DevOps, Sys Admins or someone else interested in learning key Terraform skills. Related Learning: Sign up for HashiCorp Terraform live training with Dave Prowse: HashiCorp Terraform Associate Exam Cram About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Prentice Hall, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.